Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Bumi dan Bangunan di Kota Jayapura - Enjelika Makadada; Rachmaeny Indahyani; Agustina Ester Antoh (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
This study aims to analyze the influence of the number of Tax Due Notification Letters (SPTT), land area, and Gross Regional Domestic Product (GRDP) on the revenue of Rural and Urban Land and Building Tax (PBB-P2) in Jayapura City for the 2014-2023 period. Secondary data were obtained from the Regional Revenue Agency (Bapenda) and Statistics Indonesia (BPS) of Jayapura City. The analytical method used is multiple linear regression preceded by classical assumption tests. The results show that partially, the number of SPTT has a positive and significant effect on PBB-P2 revenue, land area has a negative and significant effect, while GRDP has a positive and significant effect. Simultaneously, all three variables significantly affect PBB-P2 revenue with a coefficient of determination (R²) of 95.5 percent, while the remaining is influenced by other factors outside the model. These findings indicate the importance of strengthening tax object data collection, periodically evaluating the determination of Tax Object Sales Value (NJOP), and implementing policies that encourage regional economic growth to increase PBB-P2 revenue in Jayapura City. Keywords: PBB-P2, local tax revenue, SPTT, land area, GRDP